Chelation activity and protective effect of caulerpa lentillifera aqueous extract against lead acetate-induced toxicity in Sprague Dawley rats - Dzulsuhaimi Daud (Tanjong Malim, 2020)
Chelation activity and protective effect of caulerpa lentillifera aqueous extract against lead acetate-induced toxicity in Sprague Dawley rats by Dzulsuhaimi Daud